Effects of edible bird's nest (EBN) on cultured rabbit corneal keratocytes - Zainal Abidin, Fadhilah; Chua, Kein Hui; Ng, Sook Luan; Mohd Ramli, Elvy Suhana; Lee, Ting Hun; Abdul Ghafar, Norzana (BioMed Central, 2011)
Background There has been no effective treatment or agent that is available for corneal injury in promoting corneal wound healing. Previous studies on edible bird's nest extract (EBN) had reported the presence of hormone-like substance; avian epidermal growth factor that could stimulate cell division and enhance regeneration. This study aimed to investigate the effects of EBN on corneal keratocytes proliferative capacity and phenotypical changes. Methods Corneal keratocytes from six New Zealand White Rabbits were isolated and cultured until Passage 1. The proliferative effects of EBN on corneal keratocytes were determined by MTT assay in serum-containing medium (FDS) and serum-free medium (FD). Keratocytes phenotypical changes were morphologically assessed and gene expression of aldehyde dehydrogenase (ALDH), collagen type 1 and lumican were determined through RT-PCR. Results The highest cell proliferation was observed when both media were supplemented with 0.05% and 0.1% EBN. Cell proliferation was also consistently higher in FDS compared to FD. Both phase contrast micrographs and gene expression analysis confirmed the corneal keratocytes retained their phenotypes with the addition of EBN. Conclusions These results suggested that low concentration of EBN could synergistically induce cell proliferation, especially in serum-containing medium. This could be a novel breakthrough as both cell proliferation and functional maintenance are important during corneal wound healing. The in vitro test is considered as a crucial first step for nutri-pharmaceutical formation of EBN-based eye drops before in vivo application.